PROBLEMS MANAGEMENT OF BANKRUPT ASSETS BY THE CURATOR AFTER THE EFFECTIVE EFFECTIVE COURT DECISION - Pratama, Prila Wahyu; Nuranisa, Akila (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2023)
The management of bankrupt assets that the court has given authority to the curator and supervisory judge has difficulties and problems such as the difficulty of conducting auctions and selling assets from bankrupt assets and it is also exacerbated by the bankruptcy mafia game in playing with prices during auctions. Using the normative juridical research method, the authors found that problems had indeed occurred and there had been no harmonization of rules and not firm enough rules regarding the independence of curators and also how the management of bankruptcy assets could run more smoothly in order to create justice for the creditors of the debtor.